Risco cardiovascular em mulheres na pré e pós-menopausa - Marchi, Ricardo de (2015)
Cardiovascular diseases are the leading cause of death for women in Brazil and worldwide. Knowing the risk factors for the development of these diseases is essential to reduce this mortality. This study search to analyze the cardiovascular risk by Global Risk Score (ERG) and the prevalence of metabolic syndrome (MS) and its women component in pre-and postmenopausal women. Search also establish the association between the menopausal status and MS. This is a retrospective study in a reference outpatient clinic in cardiology in a city of Northwest Paraná, southern Brazil, which were reviewed 2052 records of asymptomatic women, attended from 2010-2014, forming two groups: women in pre-menopause, considering the women who still had menstrual cycles, regular or not; and postmenopausal women, those without menstrual cycles more than a year. For the assessment of global cardiovascular risk was used the criterion of I Brazilian Guidelines on Cardiovascular Prevention 2013 and applied the Global Risk Score (ERG). MS was characterized according to the criteria of the National Cholesterol Education Program Adult Treatment Panel III - NCEP ATP-III-2005. It was found that 51% of women at high risk, 21.3% reported a moderate risk and 27.7% had low risk. The mean total cholesterol was 193.14 mg / dl, but in the age groups 50-59 and 60 years of age they were the highest 201.1 and 193 mg / dl, respectively. The presence of diabetes mellitus (DM) was predominant in women over 60 years. The average higher blood pressure also were in the age groups 50-59 years (134.4 mmHg) and those over 60 (134.1 mmHg). Waist circumference 80 cm was found in 61.9% of women with high risk. Relating the global risk score (ERG) and the age groups, the results regarding the high risk were 0.6%, 1%, 6.1%, 12.9% and 79.4%, based on the age groups smallest to the largest. The prevalence of MS was 18.5% in perimenopausal women and 22.2% in women with postmenopausal risk of 2.75. It was also observed that the SM was more frequent with increasing age. Regarding the components of the MS, it was found that postmenopausal women showed a high risk of high density lipoproteins (HDL-C) <50 mg / dl; systolic blood pressure (SBP) 130 or diastolic blood pressure (DBP) 85 mmHg and fasting glucose ?100 mg / dl. The prevalence of DM, obesity and waist circumference was higher in women aged over 60 years while the systolic blood pressure (SBP) and total cholesterol were more prevalent in women aged 50-59 years. In women over 60 years, found a prevalence of high risk (79.4%). The prevalence of MS was higher in women after menopause compared with premenopausal